The limits of acceptable biological variation in elite athletes: Should sex ambiguity be treated differently from other advantageous genetic traits? - Boswick, J. M.; Joyner, M. J (Mayo Clinic Proceedings, 2012)
Elite athletes are unlike other people. They are gifted with the ability to be able to work their bodies faster, harder, and more skillfully than "mere mortals." While the exercise of prodigious discipline is undoubtedly key to their successes, genetic and other biological variants likely factor into world-class performances, although how they do so is both complicated and poorly understood. In this context, disorders of sexual differentiation (DSDs) can sometimes give female competitors a masculine edge. As the 2012 Olympic Games approach, one such athlete, Caster Semenya, a middle-distance runner from South Africa, has been cleared to compete, although not without considerable controversy that triggered an extensive medical work-up ordered by the International Association of Athletics Federations (IAAF) that confirmed a DSD and judged her to be a woman for the purpose of competition.